2006
DOI: 10.3354/meps307199
|View full text |Cite
|
Sign up to set email alerts
|

Fishes learn aversions to a nudibranch’s chemical defense

Abstract: The nudibranch Doriopsilla pharpa was rejected as food when tethered in the field and when offered to 2 species of co-occurring crabs (the lesser blue crab Callinectes similus and the mud crab Panopeus herbstii) and 2 species of co-occurring fishes (the mummichog Fundulus heteroclitus and the striped blenny Chasmodes bosquianus) in the laboratory. When the fishes were offered squid-based artificial food containing nudibranch extracts (i.e. defended food), both species initially consumed this food, but rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 58 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…Some predators learn to avoid sea slugs on the basis of odor. Fish are one example, and they learn in different ways to avoid the chemically defended nudibranch Doriopsilla pharpa (Long and Hay, 2006). One fish, the mummichog Fundulus heteroclitus, learns to specifically avoid sea hares via a sesquiterpene, polygodial.…”
Section: Al 2000)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some predators learn to avoid sea slugs on the basis of odor. Fish are one example, and they learn in different ways to avoid the chemically defended nudibranch Doriopsilla pharpa (Long and Hay, 2006). One fish, the mummichog Fundulus heteroclitus, learns to specifically avoid sea hares via a sesquiterpene, polygodial.…”
Section: Al 2000)mentioning
confidence: 99%
“…One fish, the mummichog Fundulus heteroclitus, learns to specifically avoid sea hares via a sesquiterpene, polygodial. In the study by Long and Hay (2006), mummichogs initially ate food containing this compound and learned to avoid food containing it, but they continued to eat foods initially associated with this compound (specific learned aversion). Another fish, the striped blenny Chasmodes bosquianus, also initially ate food containing polygodial and learned quickly to avoid food containing it; however, this species avoided food that was initially associated with polygodial but no longer contained it (generalized learned aversion).…”
Section: Al 2000)mentioning
confidence: 99%
“…Some marine natural products have been studied for their toxicity to nervous systems, but few of these investigations have determined how marine consumers sense and respond to these natural products (Derby, 2007). Even less understood is how these natural products affect a consumer's ability to learn and remember in predator-prey interactions (Lindquist and Hay, 1995;Long and Hay, 2006), and ultimately how resultant behavioral changes can impact the ecology of the organism. To stimulate further research on these topics, in this section we provide neuroecological examples that relate to the natural products we have discussed.…”
Section: Consumer Neuroecologymentioning
confidence: 99%
“…Polygodial is also found in ferns (pteridophytes), bryophytes (liverworts) (13,14), and even in animals. Studies on Mediterranean and Pacific sea slugs have shown that these animals synthesize polygodial as a chemodefensive agent to deter predatory fish (15,16). Thus, pungent sesquiterpenes are used as chemical defense agents across plant, fungal, and animal kingdoms.…”
mentioning
confidence: 99%